International joint ventures an interplay of cooperative and noncooperative games under incomplete information - Ott Ursula F (Hampshire Palgrave Macmillan, 2006)
International Joint Ventures (IJVs) combine the resources of local and foreign firms to create independent business entities that are able to avoid the risks of cross-border transactions and to gain access to new markets. Despite these advantages, the fa
Keywords: Decision making; Game theory; International business enterprises; Joint ventures; Strategic alliances(Business)